2020
DOI: 10.20944/preprints202004.0407.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>New Coronavirus (COVID-19) Pandemic: Complexities Resulting in a Tragedy.</strong>

Abstract: A striking aspect of COVID-19 is the difference in the outcome of the infection between different countries, and different ethnic groups within one country. We surveyed the literature on SARS-CoV-2 complemented with comparative publications on SARS-CoV and other coronaviruses to capture the current understanding of virus &ndash; host interactions including virus subtypes, transmission, zoonotic aspects, and potential host determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… Wu et al (2020b) agreed that potential faecal-oral transmission may pose risk in cruise ships, public transportation, hostels and dormitories but unlikely in hospitals or quarantine facilities. Although Grunig et al (2020) concluded that faecal-oral transmission had likely played a role in amplifying the pandemic in Wuhan ( Grunig et al, 2020 ), the data is based on literature review of SARS-CoV not on research investigation. On that basis, it is plausible that sewage could serve as vectors for coronavirus ( Ye et al, 2016 ; Zhang et al, 2020 ).…”
Section: Modes Of Environmental Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“… Wu et al (2020b) agreed that potential faecal-oral transmission may pose risk in cruise ships, public transportation, hostels and dormitories but unlikely in hospitals or quarantine facilities. Although Grunig et al (2020) concluded that faecal-oral transmission had likely played a role in amplifying the pandemic in Wuhan ( Grunig et al, 2020 ), the data is based on literature review of SARS-CoV not on research investigation. On that basis, it is plausible that sewage could serve as vectors for coronavirus ( Ye et al, 2016 ; Zhang et al, 2020 ).…”
Section: Modes Of Environmental Transmissionmentioning
confidence: 99%
“…Numerous researchers have attempted to assess whether sewage systems were plausible transmission pathways of coronavirus ( Barcelo, 2020 ; Gormley et al, 2020 ; Grunig et al, 2020 ). It is unlikely for SARS-CoV-2 to be transmitted via wastewater or present any significant risk of infection due to viral sensitivity to disinfectants and poor stability in environmental conditions ( Randazzo et al, 2020b ; Rimoldi et al, 2020 ).…”
Section: Modes Of Environmental Transmissionmentioning
confidence: 99%
See 1 more Smart Citation